2006
DOI: 10.1186/1471-2148-6-104
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: In order to study the dynamics of evolutionary change, 12 populations of E. coli B were serially propagated for 20,000 generations in minimal glucose medium at constant 37°C. Correlated changes in various other traits have been previously associated with the improvement in competitive fitness in the selective environment. This study examines whether these evolved lines changed in their ability to tolerate the stresses of prolonged freezing and repeated freeze-thaw cycles during adaptation to a beni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 37 publications
1
16
0
2
Order By: Relevance
“…This may be due to the fact that the water mesocosms remained frozen and did not thaw under the F–T cycle, whereas the faecal matrix, assumed to offer protection, likely experienced recrystalisation during the F–T cycling, resulting in a more detrimental effect on E. coli physiology. This would be consistent with suggestions that cell viability under freezing conditions is influenced more by repeated freeze–thawing than the duration of exposure to freezing conditions [ 33 ]. Survival curves of intestinal enterococci sourced from dairy cows and exposed to the lower F–T regime accommodated higher λ values in water relative to faeces but, as with E. coli , their final concentration in water was maintained at a higher level than the population held within the faeces.…”
Section: Discussionsupporting
confidence: 92%
“…This may be due to the fact that the water mesocosms remained frozen and did not thaw under the F–T cycle, whereas the faecal matrix, assumed to offer protection, likely experienced recrystalisation during the F–T cycling, resulting in a more detrimental effect on E. coli physiology. This would be consistent with suggestions that cell viability under freezing conditions is influenced more by repeated freeze–thawing than the duration of exposure to freezing conditions [ 33 ]. Survival curves of intestinal enterococci sourced from dairy cows and exposed to the lower F–T regime accommodated higher λ values in water relative to faeces but, as with E. coli , their final concentration in water was maintained at a higher level than the population held within the faeces.…”
Section: Discussionsupporting
confidence: 92%
“…BGI-2 was subjected to freeze thaw cycles to check its survivability/tolerance against freezing and freeze thaw cycles without the addition of any external cryoprotective agent. This test was performed by colony count method as described previously with some modifications (Sleight et al, 2006;Shivaji et al, 2013). Survivability of BGI-2 was compared with another psychrotrophic non-EPS producing Rhodococcus sp.…”
Section: Nmr Spectroscopy Of the Eps Preparationsmentioning
confidence: 99%
“…However, in many other cases parallel phenotypic changes occur not because they are advantageous, but because of relaxed selection and mutation accumulation. For example, numerous studies have shown that adaptation in the LTEE leads to a reduction in catabolic breadth and thermal-tolerance in E. coli (Bennett and Lenski 2007; Cooper et al 2001a; Cooper and Lenski 2000; Cooper et al 2001b; Leiby and Marx 2014; Sleight et al 2006). …”
Section: Realizing the Promise Of Experimental Evolutionmentioning
confidence: 99%